Osteoinductive accelerating potential of myxobacterial secondary metabolites - Hamide Parhizkari; Fatemeh Mohammadipanah; Mahshid Hodjat (The Microbe)
The increased aging population demands improved osteoblast generation in vitro for clinical treatments. Myxobacteria synthesize a wide range of biologically active secondary metabolites with unique structural features that motivated their evaluation in this study for differentiation induction of bone marrow stem cells into osteoblasts. Calcium deposition and alkaline phosphatase (AKP) enzyme activity were quantitatively measured, and the expression of osteoblastic markers and calcium nodules was determined via alizarin red staining as differentiation markers. Results showed that a myxobacterial extract induced bone marrow stem cell differentiation by increasing AKP activity, calcium deposition, osteopontin (OPN), and osteocalcin (OCN) expression. Compared to conventional osteogenesis medium, Myxobacterium UTMC 4530 metabolite extract at 0.048 μg/ml, showed 27 % higher AKP activity, as well as 13 % and 7 % higher expression of the OCN and OPN genes, respectively. Despite ultralow concentrations, Myxobacterial extract induces a high level of differentiation, which may make it a valuable source of assessment for developing potent in vitro inducers of bone marrow stem cells which may have therapeutic potential in the future by promoting osteogenesis